In vitro characterization and in vivo performance of mefenamic acid-sodium diethyldithiocarbamate based liposomes - Jarrar, Qais Bashir Mahmoud; Abdullah, Muhammad Nazrul Hakim; Cheema, Manraj Singh; Zakaria, Zainul Amiruddin (Universidade de Sao Paulo, 2019)
Mefenamic acid (MFA) is a hydrophobic drug with low dissolution rate. This study aimed to develop stable and reproducible aqueous formulations of MFA using liposomes as drug carriers. The drug entrapment, particles size and drug release profiles, and stability and reproducibility of the liposomes were determined. In addition, the maximum tolerated dose (MTD) was determined in rats via the oral and intraperitoneal routes of administration. Also, the anti-inflammatory efficacy of these liposomes was evaluated using carrageenan-induced paw edema model in rats. MFA-DDC based liposomes demonstrated a drug entrapment efficacy of 93.6%, particles size of 170.9 nm, and polydispersity index of 0.24 which were not statistically affected when stored in room and refrigerated temperatures for at least 4 weeks. The MTD of the intraperitoneally administrated MFA-loaded liposomes was 20 mg MFA/kg, whereas for those of oral administrations, it was up to 80 mg MFA/kg. Intraperitoneal dose (80 mg MFA/kg) of MFA-DDC liposomes induced extrapyramidal symptoms associated with significant elevation in serum potassium and muscle enzymes. Moreover, significant inhibition of paw edema was demonstrated by the oral and intraperitoneal routes. These findings suggest that MFA-DDC based liposomes are an effective formulation of MFA and recommend the use of bioequivalence assessments with commercial formulations.